An energy‐efficient and balanced clustering approach for improving throughput of wireless sensor networks. (31st October 2019) - Karmaker, Amit; Alam, Mohammad Shah; Hasan, Md. Mahedee; Craig, Andrew
Summary: Maximizing the lifespan of wireless sensor networks is currently drawing a lot of attention in the research community. In order to reduce energy consumption, sensor nodes that are far from the base station avoid sending data directly. As a result, several disjoint clusters are formed, and nodes within a cluster send their data through the cluster head to avoid long transmissions. However, several parameters related to transmission cost need to be considered when selecting a cluster head. While most of the existing research work considers energy and distance as the most stringent parameters to reduce energy consumption, these approaches fail to create a fair and balanced cluster. Consequently, unbalanced clusters are formed, resulting in the degradation of overall performance. In this research work, a cluster head selection algorithm is proposed that covers all parts of the sensing area in a balanced manner, saving a significant amount of energy. Furthermore, a capture effect–based intracluster communication mechanism is proposed that efficiently utilizes the time slot under various traffic conditions. A Näive Bayes classifier is used to adapt the window size dynamically according to the traffic pattern. Finally, a simulation model using OMNeT++ is developed to compare the proposed approach with the pioneer clustering approach, LEACH, and the contemporary LEACH‐MAC protocol in terms of performance. The results of the simulation indicate that the proposed approach improves the overall performance in terms of network lifetime, energy efficiency, and throughput. Abstract : A novel cluster head selection scheme in Wireless Sensor Networks which forms cluster in a more balanced manner and thereby reduces overall energy consumption significantly. A capture effect based intra‐cluster communication technique achieves high throughput. Finally, a dynamic window based channel access scheme ensures better channel utilization adaptive to various traffic loads.